EXPERIENCES OF NEWCOMERS TO FRANSASKOIS SCHOOLS: OPPORTUNITIES FOR COMMUNITY COLLABORATION - Carlson Berg, Laurie Diane (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
ABSTRACT. Recently, there has been an unprecedented increase in the number of Francophone immigrants to Anglo-dominant provinces in Canada. This paper presents results of an appreciative inquiry-based study into the experiences of newcomers to one Francophone community in a linguistic minority context (Saskatchewan). Transcripts of interviews with twenty-seven participants were analysed to identify potential barriers to inclusion in the Francophone school community. Recommendations are offered as to how culturally reciprocal collaboration and mentoring may be used to address identified challenges. LES EXPÉRIENCES DES NOUVEAUX-VENUS DANS LES ÉCOLES FRANSASKOISES: DES OPPORTUNITÉS DE COLLABORATION COMMUNAUTAIRE RÉSUMÉ. Il y a eu récemment une augmentation sans précédent du nombre d’immigrants francophones dans les provinces à prédominance anglophone au Canada. Cet article présente les résultats d’une étude par investigation appréciative auprès de nouveaux-venus au sein d’une communauté francophone dans un contexte de minorité linguistique (Saskatchewan). Les comptes-rendus de vignt-sept participants ont été analysés afin d’identifier les obstacles potentiels à leur inclusion dans la communauté scolaire francophone. Des recommandations sont formulées, expliquant de quelle manière la collaboration mutuelle entre les cultures et le mentorat peuvent aider à résoudre les problématiques identifiées.